Computational study of the rate constants and free energies of intramolecular radical addition to substituted anilines - Gansäuer, Andreas; Seddiqzai, Meriam; Dahmen, Tobias; Sure, Rebecca; Grimme, Stefan (Beilstein Journal of Organic Chemistry, 2013)
The intramolecular radical addition to aniline derivatives was investigated by DFT calculations. The computational methods were benchmarked by comparing the calculated values of the rate constant for the 5-exo cyclization of the hexenyl radical with the experimental values. The dispersion-corrected PW6B95-D3 functional provided very good results with deviations for the free activation barrier compared to the experimental values of only about 0.5 kcal mol−1 and was therefore employed in further calculations. Corrections for intramolecular London dispersion and solvation effects in the quantum chemical treatment are essential to obtain consistent and accurate theoretical data. For the investigated radical addition reaction it turned out that the polarity of the molecules is important and that a combination of electrophilic radicals with preferably nucleophilic arenes results in the highest rate constants. This is opposite to the Minisci reaction where the radical acts as nucleophile and the arene as electrophile. The substitution at the N-atom of the aniline is crucial. Methyl substitution leads to slower addition than phenyl substitution. Carbamates as substituents are suitable only when the radical center is not too electrophilic. No correlations between free reaction barriers and energies (ΔG‡ and ΔGR) are found. Addition reactions leading to indanes or dihydrobenzofurans are too slow to be useful synthetically.
Keywords: aromatic substitution; computational chemistry; DFT-D3; free radical; polar effects; radical reaction